2015
DOI: 10.1007/s00167-015-3703-8
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the articular branch of the lateral pectoral nerve to the shoulder joint

Abstract: The articular branch of the LPN to the shoulder, as well as the muscular and cutaneous branches of the LPN, covers a portion of the shoulder joint with suprascapular and axillary nerves. Surgeons might consider a peripheral block of the suprascapular, axillary, and LPNs to provide maximum block coverage after shoulder joint surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…[1][2][3][4] Innervation of the GHJ can be divided into anterior and posterior innervation from articular branches of the suprascapular nerve (SN) (posterior-lateral), axillary nerve (AN) (anterior-lateral, inferior, and posterior-lateral), and lateral pectoral nerve (LPN) (anteriorsuperior). 5,6 These nerves also provide substantial motor innervation. Considering the burden of shoulder pain worldwide, the potential to provide nerve blocks and neuroablative treatments with minimal weakness warrants serious consideration.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4] Innervation of the GHJ can be divided into anterior and posterior innervation from articular branches of the suprascapular nerve (SN) (posterior-lateral), axillary nerve (AN) (anterior-lateral, inferior, and posterior-lateral), and lateral pectoral nerve (LPN) (anteriorsuperior). 5,6 These nerves also provide substantial motor innervation. Considering the burden of shoulder pain worldwide, the potential to provide nerve blocks and neuroablative treatments with minimal weakness warrants serious consideration.…”
mentioning
confidence: 99%
“…[6][7][8][9] The LPN has gained attention for chest wall and postmastectomy pain 10 but is underrecognized as a contributor to shoulder structures. Anatomical studies describe the LPN originating from C5-7 nerve roots, supplying innervation to the skin over the subacromial bursa, 5,11 muscular innervation of the pectoralis major and deltoid muscles, 5 and intra-articular innervation to the ACJ 3,4 and anterior GHJ. 5,6,11 Innervation of the ACJ and GHJ via articular branches of the LPN has potential for peripheral nerve blockade, 5,6 similar to AN and SN blocks.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The key landmarks identified include the coracoid process, midpoint between the suprascapular and spinoglenoid notches, rim of the anterior glenoid fossa, and acromial branch of the thoracoacromial artery. In previous studies, Nam et al 15 reported the course of the articular branch from LPN in relation to the coracoid process and coracoclavicular ligament,15 and Eckmann et al 16 related the articular branches of SSN, LPN and AN to the spine of scapula, thoracoacromial artery and head of humerus, respectively 16…”
Section: Discussionmentioning
confidence: 99%